Design of experiment on transformer efficiency Michelle V. Mancenido, Rolly D. Ben, Juvilyn M. Masilungan. - Mancenido, Michelle V. (College of Engineering, 2001)
Northeastern Trans is a transformer-manufacturing enterprise which holds operations in Novaliches, Metro Manila. In layman's terms, a transformer is an electrical device used to "step up" or "step down" voltages. Its measure of quality and excellence is the percent efficiency it attains after subtracting all power losses due to faults in manufacture. This team has expressed the main objective of this study as the determination of the factors producing a significant effect on the power losses, and subsequently, the efficiency of the transformer system. The study commenced from PROBLEM ANALYSIS, where the main deviation (LOW TRANSFORMER EFFICIENCY) and the factors leading to this deviation are identified. Methods Engineering tools were employed such that to isolate the factors bearing the most impact, a PARETO CHECK SHEET and an equivalent PARETO GRAPH were used. Among the four factors identified by the management, two stood out from the PARETO analysis : OIL TYPE and INSULATING MATERIAL TYPE. With the two main factors already identified, a DESIGN OF EXPERIMENT was in hand. This study utilized a fixed effects model for a two factor factorial design. The response variable was identified as a system's power loss, and the treatments as OIL TYPE (A) and INSULATING MATERIAL (B). An analysis of variance through the employment of the F-TEST STATISTICAL TABLE determined which main factors and factor combindations are significant. From this test of significance, TREATMENT (2), the insulating material type, was determined to have a significant effect. Statistical tools sch as the Operating Characteristic curves determined the sufficiency of the sample size and the power of test (1-B). With a replicate number of 3, the power of the test was calculated to be 0.985, hence, implying the sufficiency of the current sample size at a large power magnitude. From the computation of the sample coefficient to determine the adequacy of the model, a more than sufficient value of 83 percent suggested a high correlation for the design. The team has recommended the use of MINERAL OIL and CLASS 105 type of insulating material, as this has been proven to result to the least possible value of power losses. The team has also presented subjective recommendations for process improvement regarding the factors which were not covered by statistical analysis.